Gastrointestinal Distension by Pectin-Containing Carbonated Solution Suppresses Food Intake and Enhances Glucose Tolerance via GLP-1 Secretion and Vagal Afferent Activation - Ohbayashi, Kento; Oyama, Yukiko; Yamaguchi, Chiharu; Asano, Toshiki; Yada, Toshihiko; Iwasaki, Yusaku (Frontiers in Endocrinology, 2021)
Diet-induced gastrointestinal distension is known to evoke satiation and suppress postprandial hyperglycemia; however, the underlying mechanisms remain poorly understood. This study explored how gastrointestinal distension regulates energy homeostasis by using inflating stomach formulation (ISF), the carbonated solution containing pectin that forms stable gel bubbles under acidic condition in the stomach. Here we show that, in mice, oral administration of ISF induced distension of stomach and proximal intestine temporarily, stimulated intestinal glucagon-like peptide-1 (GLP-1) secretion, and activated vagal afferents and brainstem. ISF suppressed food intake and improved glucose tolerance via enhancing insulin sensitivity. The anorexigenic effect was partially inhibited, and the beneficial glycemic effect was blunted by pharmacological GLP-1 receptor blockade and chemical denervation of capsaicin-sensitive sensory nerves. In HFD-fed obese mice showing arrhythmic feeding and obesity, subchronic ISF treatment at the light period (LP) onset for 10 days attenuated LP hyperphagia and visceral fat accumulation. These results demonstrate that gastrointestinal distension by ISF stimulates GLP-1 secretion and the vagal afferent signaling to the brain, thereby regulating feeding behavior and glucose tolerance. Furthermore, subchronic ISF treatment ameliorates HFD-induced visceral obesity. We propose the diet that induces gastrointestinal distension as a novel treatment of hyperphagic obesity and diabetes.